2022
DOI: 10.1126/sciadv.add5051
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic microbes aid host adaptation by metabolizing a deterrent host pine carbohydrate d -pinitol in a beetle-fungus invasive complex

Abstract: The red turpentine beetle (RTB) is one of the most destructive invasive pests in China and solely consumes pine phloem containing high amounts of d -pinitol. Previous studies reported that d -pinitol exhibits deterrent effects on insects. However, it remains unknown how insects overcome d -pinitol during their host plant adaptation. We found that d -pinitol had an antagonistic effect on RTB, which mainly relied on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 68 publications
2
37
0
1
Order By: Relevance
“…Our previous studies found that AMYG and SUC1 were involved in the hydrolyzation of starch to D-glucose, and iolT1, MIOX, PDA6, PDA9-1, and PDA9-2 participated in the D-pinitol utilization. 7,13 Consistent with our carbohydrate metabolic results, there were no differences in the genes involved in the starch to D-glucose conversion and D-pinitol metabolism between WT and ΔGpr-1 mutant, which suggested that Gpr-1 was not involved in the carbohydrate metabolism in L. procerum (Figure S5). As noted in the preceding results, loss of Gpr-1 caused a thicker cell wall of L. procerum.…”
Section: ■ Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Our previous studies found that AMYG and SUC1 were involved in the hydrolyzation of starch to D-glucose, and iolT1, MIOX, PDA6, PDA9-1, and PDA9-2 participated in the D-pinitol utilization. 7,13 Consistent with our carbohydrate metabolic results, there were no differences in the genes involved in the starch to D-glucose conversion and D-pinitol metabolism between WT and ΔGpr-1 mutant, which suggested that Gpr-1 was not involved in the carbohydrate metabolism in L. procerum (Figure S5). As noted in the preceding results, loss of Gpr-1 caused a thicker cell wall of L. procerum.…”
Section: ■ Resultssupporting
confidence: 87%
“…The growing evidence has shown that associated microbes are required for growth, reproduction, host and environment adaptation, pesticide resistance, and triple interactions with plant and natural enemies of various destructive pests. 6,7,38 For example, primary endosymbiont Buchnera is required for the survival of its host aphid as it provides essential amino acids to its host. 38 Our serial studies on the RTB-L. procerum invasive complex have shown that L. procerum contributes to the outbreak of RTB in China from multiple aspects including pathogenicity, 3-carene induction, nutritional compensation, and deterrent degradation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations